Separation of Empetrum nigrum Compounds and Their Anti-microbial Effects on Common Bacterial Species - Evans, Amy (1899)
Empetrum nigrum, crowberry, is an arctic shrub known to have anti-microbial activity against Mycobacterium species and nine fungal species. Several compounds have been identified from the berries and the branches of E. nigrum. This report examines the separation of compounds from E. nigrum leaves and branches and the effects crude extracts have on common laboratory bacterial species. Crude extracts of the plant were obtained by soaking plants in solvents of various polarities. The methanol extract was further separated using reverse phase flash column chromatography. Following a reaction to remove glucose from a compound, NMR spectra were used to characterize the compound as an aromatic. The anti-microbial activities of the methanol and water extracts were tested in this project using inhibition assays. The methanol extract of the leaves and branches showed the most activity against Gram-negative bacteria. Further tests showed that the inhibition of Gram-negative bacterial growth increased as the amount of extract increased from 10 pi to 30 pi per disk. Tests also showed that the methanol extract did not affect the growth of Mycobacterium smegmatis. This project is an initial step in the long process of developing new pharmaceuticals and may prompt further investigation into the anti-microbial properties of E. nigrum.